Process optimization for recycling of bread waste into bioethanol and biomethane: a circular economy approach - Narisetty, Vivek; Nagarajan, Sanjay; Gadkari, Siddharth; Ranade, Vivek V.; Zhang, Jingxin; Patchigolla, Kumar; Bhatnagar, Amit; Awasthi, Mukesh Kumar; Pandey, Ashok; Kumar, Vinod (Elsevier, 2022)
Bread is the second most wasted food in the UK with annual wastage of 292,000 tons. In the present work, bread waste (BW) was utilized for fermentative production of ethanol by Saccharomyces cerevisiae KL17. Acidic and enzymatic saccharification of BW was carried out resulting in the highest glucose release of 75 and 97.9 g/L which is 73.5 and 95.9% of theoretical yield, respectively. The obtained sugars were fermented into ethanol initially in shake flask followed by scale up in bioreactor in batch and fed-batch mode. In the fed-batch mode of cultivation, the maximum ethanol titers of 111.3, 106.9, and 114.9 g/L with conversion yield and productivity of 0.48, 0.47, and 0.49 g/g, and 3.1, 3.0, and 3.2 g/L.h was achieved from pure glucose, glucose-rich acidic and enzymatic hydrolysates, respectively. Further to improve the process economics, the solid residues after acidic (ABW) and enzymatic (EBW) hydrolysis of BW along with respective fermentation residues (FR) obtained after the ethanol production were pooled and subjected to anaerobic digestion. The solid residue from ABW + FR, and EBW + FR yielded a biochemical methanation potential (BMP) of 345 and 379 mL CH4/g VS, respectively. Life cycle assessment of the process showed that the total emissions for ethanol production from BW were comparable to the emissions from more established feedstocks such as sugarcane and maize grain and much lower when compared to wheat and sweet potato. The current work demonstrates BW as promising feedstock for sustainable biofuel production with the aid of circular biorefining strategy. To the authors knowledge, this is the first time, such a sequential system has been investigated with BW for ethanol and biomethane production. Further work will be aimed at ethanol production at pilot scale and BMP will be accessed in a commercial anaerobic digester.
Keywords: Bread waste; Saccharification; Bioethanol; Saccharomyces cerevisiae; Biomethane; Life cycle assessment